Photochemical and detoxifying properties of humic substances in water solution - Sokolova, I. V.; Tchaikovskaya, O. N.; Bryantseva, N. G.; Nechaev, L. V.; Vershinin, N. O. (Видавництво Львівської політехніки, 2013)
The degradation of herbicides 4-chloro-2-methylphenoxyacetic acid (MCPA) and 2,4- dichlorophenoxyacetic acid (2,4-D) in water by the combination of UV-irradiation and humic acids has been studied. The photoreaction rate of all irradiated samples was lowest for the sample irradiated at 308 nm in the absence and in the presence of humic acids (HAs), and highest for the sample irradiated at 222 nm. HAs apparently catalyzed the formation some different not toxic photoproducts of 2,4-D and MCPA after UV-irradiation treatment by excilamps. We have observed a dependence of the detoxification both on the structure of the studied compounds and on the characteristics of the source. Изучена деградация гербицидов 4-хлор-2-метилфеноксиуксусной (MCPA) и 2,4- дихлорфеноксиуксусной (2,4-D) кислот в воде под действием УФ-излучения эксиламп и гуминовых кислот. Скорость фотореакции ниже в случае облучения длиной волны 308 нм как в присутствии, так и без гуминов и наивысшая при облучении длиной волны 222 нм. Гуминовые кислоты способствуют образованию нетоксичных фотопродуктов. Обнаружена зависимость эффективности детоксикации как от структуры исследованных соединений, так и от характеристик источника облучения.